2021
DOI: 10.29219/fnr.v65.7807
|View full text |Cite
|
Sign up to set email alerts
|

Screening of potential tropical fruits in protecting endothelial dysfunction in vitro

Abstract: Background: High consumption of antioxidant-rich fruits and vegetables reduces the endothelial damage involved in cardiovascular disease pathogenesis. Objective: To evaluate the phytochemical content, antioxidant and scavenging activities (FRAP, ORAC, OH•, HOCl, H2O2, and O2−), endothelial H2O2-cytoprotective effect, nitric oxide (NO) release activation potential, and endothelial wound healing properties of 10 tropical fruits, comprising pineapple, sugar apple, papaya fruit, longan, mangosteen, lychee, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Several natural compounds reduce the formation of AGEs mainly by trapping the active dicarbonyl compounds, regulating RAGE, or scavenging ROS ( Song et al, 2021 ). UCP exerts high antioxidant potential by scavenging excessive ROS, thus protecting against MGO-induced fibroblast oxidative stress ( Wattanapitayakul et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several natural compounds reduce the formation of AGEs mainly by trapping the active dicarbonyl compounds, regulating RAGE, or scavenging ROS ( Song et al, 2021 ). UCP exerts high antioxidant potential by scavenging excessive ROS, thus protecting against MGO-induced fibroblast oxidative stress ( Wattanapitayakul et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that unripe Carica papaya L. (UCP) fresh fruit extract has a high antioxidant capacity, protecting endothelial cells against oxidative stress ( Jarisarapurin et al, 2019 ). UCP contains well-known antioxidants such as ascorbic and gallic acids and quercetin ( Wattanapitayakul et al, 2021 ). Therefore, we investigated whether UCP could protect against fibroblast oxidative stress induced by MGO, which serves as a model of dicarbonyl stress in diabetic skin deterioration.…”
Section: Introductionmentioning
confidence: 99%
“…Similar effects were observed with interventions of phloretin (Ren et al, 2016 ). Apple extract (AE) elevated nitrite production, and increased wound closure of endothelial cells damaged by H 2 O 2 (Wattanapitayakul et al, 2021 ). AE treatments had a protective effect on human umbilical vein endothelial cells (HUVEC) exposed to cytotoxic glycosylated protein GFBS/FeCl 3 .…”
Section: The Beneficial Health Effects Of Applesmentioning
confidence: 99%
“…Flavonols have numerous cardioprotective properties, such as platelet stabilization, anti-inflammatory, antidiabetic, antihypertensive, and hypocholesterolemic activity [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. To the best of our knowledge, quercetin is the most widely distributed and well-known flavonol obtained from natural sources, as well as the best-studied flavonol, in both in vitro and in vivo studies [ 51 ].…”
Section: Flavonols and Their Cardioprotective Activitymentioning
confidence: 99%